H2 sensing characteristics in glass-removed amorphous Co60.51Fe3.99Cr12.13B13.53Si9.84 microwires. (September 2019) - El-Demrdash, S.A.; Adam, A.M.; Panina, L.V.
Highlights: Glass coated microwires of Co60.51 Fe3.99 Cr12.13 B13.53 Si9.84 have been prepared using the Taylor–Ulitovski technique. Electrical resistance of the wires as a function of time intervals after H2 exposure was measured. Hysteresis loop of the concerned wires was measured before and after H2 expouser. Abstract: Hydrogen sensing is crucial to ensure safety in near-future zero-emission fuel cell powered vehicles and many other areas of industry. In this work, we present a novel hydrogen sensor based on the glass removed microwires. Using microwire as Hydrogen gas sensor gives a promising result with high sensitivity, high response and ultralow power consumption. Microwires are tiny, very light and commercially available, hence, sensors based on microwires can widely be produced. In this manuscript, we report on sensitivities and response times of such sensors as a function of the change in hydrogen (H2 ) concentration at standard conditions of room temperature and atmospheric pressure. It was found that the wire is able to detect H2 of concentrations even lower than 0.05% within 1 s at the onset of the diffusion using only a few amounts of power, matching the commercial requirements for H2 safety sensors. Thermodynamic chemistry is used to explain the effect of hydrogen on the wire. Magnetic properties, in terms of, "hysteresis loop curves" of the wire are investigated. From hysteresis loops measurements, it was observed that there is no change occurring in the magnetic properties of the samples in response to hydrogen exposure, a matter confirming and matching the data provided by thermodynamics. As a direct result of the high response, simplicity of fabrication and time recovery, the proposed material is very promising for practical H2 sensing applications.